2021
DOI: 10.1002/ange.202103710
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of an Enantiopure Sub‐monolayer of Helicene Radical Cations on a Au(111) Surface through Noncovalent Interactions

Abstract: In the past few years, the chirality and magnetism of molecules have received notable interest for the development of novel molecular devices. Chiral helicenes combine both these properties, and thus their nanostructuration is the first step toward developing new multifunctional devices. Here, we present a novel strategy to deposit a sub‐monolayer of enantiopure thia[4]helicene radical cations on a pre‐functionalized Au(111) substrate. This approach results in both the paramagnetic character and the chemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…Quantitative knowledge of medium effects on the redox behaviour of helicenes allows its rational manipulation and better design of applications, e. g. for their use as chiral spin filters, which is currently under development in our group. [16] We believe that the distinctive properties of these molecules will attract many researchers, in the light of the synthetic accessibility in continuing improvement in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative knowledge of medium effects on the redox behaviour of helicenes allows its rational manipulation and better design of applications, e. g. for their use as chiral spin filters, which is currently under development in our group. [16] We believe that the distinctive properties of these molecules will attract many researchers, in the light of the synthetic accessibility in continuing improvement in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Helical shaped bis-phenothiazines, like derivatives 1-9 prepared for this study, have found interesting opportunities in material science [11,16] and a detailed quantitative investigation of their red-ox one-electron properties appeared a mandatory step to underpin their peculiar characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 29 ] Additionally, Sessoli's employment of chirality‐induced spin selectivity has demonstrated its efficiency in spin‐specific electron transport. [ 30 ] Overall, the use of open‐shell macroradicals in spintronics has shown great promise in recent years. Their unique electronic properties make them a promising candidate for numerous spin‐based electronic devices.…”
Section: New Class Materials For Organic Spintronicsmentioning
confidence: 99%
“…The availability of differently functionalized enantiomerically pure helicenes, avoiding the limitation associated with chiral HPLC resolution [17,23] is mandatory for the development of the appealing applications of these peculiar systems [21,22,24]. Therefore, in recent years we tried to set off regio-, stereo-and enantioselective synthetic approaches for the preparations of 1.…”
Section: Introductionmentioning
confidence: 99%